ChemInform Abstract: Dipolar and V‐Shaped Structures Incorporating Methylenepyran and Diazine Fragments. Issue 37 (16th September 2014) - Achelle, Sylvain; Kahlal, Samia; Saillard, Jean‐Yves; Cabon, Nolwenn; Caro, Bertrand; Robin‐le Guen, Francoise
Abstract Various novel dipolar V‐shaped chromophores are prepared via condensation of methylenepyran aldehydes and methylpyrimines.